Microfiche digitization and retrieval process improvement for the human relations area files collection of the Rizal library, Ateneo de Manila University - Dela Cruz, Tommy M.; Dorado, Dan Anthony D.; Olgado, Benedict S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2018)
This project converted the microfiche copy of the Human Relations Area Files (HRAF) collection of the Rizal Library to PDF format. The HRAF is a primary source of more than 300 cultures and societies around the world and serves anthropologists and other related scientists.
The collection is composed of 17,664 pieces of microfiche. It is accompanied by a set of almost 2,600 Author-title and subject finding aids that covers all 11 series of the collection, and are printed on index cards placed in the card catalog. Some of the microfiches are already deformed and exposed to dust and thus needed digitization. This gave the need for it to be digitized, leading to this project.
This was implemented in collaboration with the Microforms and Digital Resources Center, Photoduplication Section and Computer Services. Adequate budgeting for the project was provided by the Rizal Library through the Director's office. Three two-terabyte capacity hard-disk drives were used to accommodate the scanned images. The Flex-Scan Microfiche and Microfilm was used for the scanning. Desktop computers and other infrastructures were provided by the Computer Services Section.
More than 17,600 microfiches were scanned and converted into PDF format. The HRAF-microfiles were first passed through an inventory. Each microfiche card was carefully examined for possible damage such as thorns, scratches, cuts, tears, and folds. Wrongly filed and missing microfiches were also noted. Dusts were removed with the use of soft cotton. Along with that, a total of 1,370 entries was encoded. This project provided the users a systematic indexing process with computerized finding aids created or modified based on the required fields. The digitized version of the HRAF-microfiles were made available for access inside the Ateneo de Manila Campus while the microfiche copies of the HRAF-microfiles were preserved to non-acidic archival boxes.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Microfiche -- Digitization; Digitization; Ateneo de Manila University, Rizal Library -- Digitization